STORYTELLING: ONE PACKAGE LEARNING IN IMPROVING LANGUAGE SKILL AND IMPLANTING CHARACTER EDUCATION ON CHILDREN - Hidayati, Niswatin Nurul (EDUKASI: Jurnal Pendidikan Islam, 2019)
The development of technology makes the world become narrow and various kinds of information and shows become easy to access, including by children. Various kinds of acts of violence, crime, even videos or content that are not yet suitable for children to watch are more easily accessible through devices. This has a negative impact on the lives of the nation's children, for example theft, sexual violence, and brawl committed by children and adolescents. Thus, the inculcation of moral values by both parents and teachers becomes a "must" thing to do so that the next generation of the nation is maintained. If we talk about implanting moral values on children, we surely need the right media to use. One way is by storytelling. By listening to stories, directly or not, children will absorb the moral values of what they hear. In addition, knowledge of the vocabulary of a language will be absorbed by children. We know that there are golden ages in children where children have periods where their brains are like sponges that are able to absorb many things. This paper was a literature study that discussed the correlation between storytelling in the process of improving language skills and implanting moral values on children. Based on several available sources, it can be concluded that the use of storytelling as a medium was an effective thing to use on children.